LEGAL CULTURE AS A KEY FACTOR IN ENSURING THE RULE OF LAW IN THE STATE (World Bulletin of Management and Law, 2023)
Legal culture plays a crucial role in ensuring the rule of law in any state. It encompasses the attitudes, values, and beliefs that shape people's understanding of the law and their relationship with it. A strong legal culture promotes a responsible attitude towards one's actions and respect for the rights of others, encouraging citizens to participate actively in public life. Without a culture of lawfulness, a society cannot function effectively, as people may be more prone to break the law and ignore the rights of others. This article explores the significance of legal culture in maintaining law and order in the state. The author draws attention to the role of legal culture in the formation of citizenship, democracy, and civil society, all of which are vital factors for promoting a lawful society. The article highlights the value of respecting the rights of others and active participation in public life as essential components of legal culture. Moreover, the article emphasizes the importance of high levels of legal culture in reducing crime rates and ensuring the effective operation of law enforcement agencies. It recognises that a society where citizens have a strong legal culture is ultimately more likely to obey the law, cooperate with law enforcement agencies, and contribute to the general maintenance of law and order